Analysis of sensitivity and resolution in plasmonic microscopes - Pechprasarn, Suejit (2012)
Surface plasmons (SP) are guided electromagnetic wave propagating along the surface of metal. The properties of SP are affected by the material attached to the metallic surface so they can be used as a very sensitive sensor capable of detecting the deposition of subnanometric layers of dielectric. SP has been widely investigated for biosensor applications and the theory is well established.